Pengaruh Net Profit Margin Dan Earning Per Share Terhadap Harga Saham pada PT. Dyandra Media International, Tbk - Afriyani; Eka Ananda; Adriani Yasin, Nurfatwa (Jurnal Online Manajemen ELPEI, 2025)
This study aims to determine the effect of Net Profit Margin and Earning Per Share on Stock Prices at PT. Dyandra Media International, Tbk. The types of data used in this study are quantitative data and qualitative data. The analysis method used is multiple linear regression, coefficient of determination, correlation coefficient, and T-test F-test. Regression Calculation Results Y = 94.705 + 0.414X1 + 0.083X2, coefficient of determination R2 = 64.1%, correlation coefficient r = 0.800, thus it can be concluded that Net Profit Margin and Earning Per Share simultaneously have no significant effect on Stock Prices at PT. Dyandra Media International, Tbk. Partially Net Profit Margin has a positive and insignificant effect on Stock Prices at PT. Dyandra Media International, Tbk and Earning Per Share has a positive and insignificant effect on Stock Prices at PT. Dyandra Media International, Tbk.